Animasi 3D Rute Jalur Bus Trans Jogja Trayek 1A Dan 3A Berbasis Android - Retnowati, Nurcahyani Dewi (Sekolah Tinggi Teknologi Adisutjipto, 2017)
The increase in the number of foreign tourists who are interested in visiting DIY significantly because this region has various world-class attractions, one of which is Malioboro. Currently, tourist infrastructure such as road access, transportation, and revitalization Malioboro has been built so as to facilitate the tourists and local tourists to travel to Malioboro. Transportation facilities that facilitate the tourists one of them is Trans Jogja bus. Trans Jogja bus route that supports transportation from the airport to Malioboro is Trans Jogja bus with route 1A and route 3A so that needed a medium that can give information of bus route of Trans Jogja from Airport to Malioboro and vice versa. The media in the form of three-dimensional animation based on mobile android that can be more informative, making it easier for tourists to understand the route of Trans Jogja bus route. Making interactive media using 3ds max software with motion tween animation concept. the design and concept is then implemented in the form of animated movie. Application testing using black-box testing method. the results of the test show that the application is running well, the button on the application can be used, the route shown in accordance with the conventional map and can show the routes of bus routes according to the route used.